A Simulation Based Study for the Early Detection of Glaucoma Using Temperature Profiling of Human Eye (Dhaka University Journal of Science, 2020)
Glaucoma is one of the leading ophthalmologic disorders worldwide which results in irreversible blindness if left untreated. Although many detection techniques are already in use, they prove to detect glaucoma at a later stage when the disease causes irreversible effects to the optic tissue. This work aims at developing a novel technique to detect the presence and progression of glaucoma at an early stage through temperature profiling of optic tissues by LASER radiation. A 3D CAD model of the real human eye designed in SolidWorksTM was used and different parameter values were defined for performing thermal simulation in COMSOL Multiphysics® for three distinct LASER point sources: 694.3 nm Ruby LASER, 1064 nm Nd:YAG LASER and 1340 nm Nd:YAP LASER. By analyzing the thermal profile obtained from the simulation, an inverse trend of temperature variation with progression of glaucoma was observed. The effect was most prominently observed in using 694.3mm Ruby LASER with no such temperature rise in the eye causing any physiological harm. This work shows the possibility of using temperature profile due to irradiated light on human eye as a novel biomarker for the early detection of glaucoma.Dhaka Univ. J. Sci. 68(1): 37-44, 2020 (January)